Numerical De-embedding of Periodic Guided-wave Structures via SOL/SOC in FEM Algorithm - Yin Li; Danpeng Xie; Lei Zhu (Applied Computational Electromagnetics Society Journal (ACES), 2019)
This paper presents a 3D full-wave finite element method (FEM) combined with short-open-load (SOL) and short-open calibration (SOC) technique. Due to the effective calibration of the port discontinuities between the feeding line and periodic structure, both SOL and SOC can successfully extract the intrinsic unite-length parameters, i.e., complex propagation constants and effective characteristic impedances. Distinctively, the SOL can be easily implemented with the commercial software such as Ansys HFSS, which is widely applicable for various kinds of periodic structure. More importantly, the SOC incorporated within the FEM algorithm intrinsically reduces the requirement of the load standard in SOL. Also, the SOC in FEM will be independent with the absorbing boundary condition at the port. And the port information such as characteristic impedance and propagation constants at the designated port will not be required in advanced, thereby allowing the arbitrary implementation of non-uniform feeding structures. In order to demonstrate the efficiency and accuracy of our proposed approaches, two numerical examples are given out for verification.